Drosophila chorion genes: cracking the eggshell's secrets. - Orr-Weaver, T.L. (BioEssays, 1991)
The chorion genes of Drosophila are amplified in response to developmental signals in the follicle cells of the ovary prior to their transcription. Their expression is regulated both temporally and spatially within this tissue. They thus serve as models both for the regulation of DNA replication and of developmental transcription. The regulatory elements for DNA amplification have been delineated. Their analysis reveals that amplification is mediated by several regulatory regions and initiates at defined origins within the chorion cluster. Proteins involved in amplification are being identified both by mutations affecting amplification and by DNA binding studies. Regulatory elements for temporal as well as spatial control of chorion gene expression have been characterized, and two candidate transcription factor genes have been cloned.